2017
DOI: 10.2147/tcrm.s143809
|View full text |Cite
|
Sign up to set email alerts
|

Role of heart-rate variability in preoperative assessment of physiological reserves in patients undergoing major abdominal surgery

Abstract: BackgroundMajor abdominal surgery (MAS) is associated with increased morbidity and mortality. The main objective of our study was to evaluate the predictive value of heart-rate variability (HRV) concerning development of postoperative complications in patients undergoing MAS. The secondary objectives were to identify the relationship of HRV and use of vasoactive drugs during anesthesia, intensive care unit length of stay (ICU-LOS), and hospital length of stay (H-LOS).Patients and methodsSixty-five patients sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 46 publications
0
17
1
1
Order By: Relevance
“…Besides the proposed influence of low HRV on survival of colorectal cancer patients through development and increased progression of cancer, Reimer et al suggested that low HRV could influence survival of those undergoing surgical treatment due to more-and more severe post-operative complications [15]. However, the results found in this study were not concurrent with those of Reimer et al who included 53 patients with ASA > 1 undergoing elective surgery.…”
Section: Plos Onecontrasting
confidence: 73%
See 1 more Smart Citation
“…Besides the proposed influence of low HRV on survival of colorectal cancer patients through development and increased progression of cancer, Reimer et al suggested that low HRV could influence survival of those undergoing surgical treatment due to more-and more severe post-operative complications [15]. However, the results found in this study were not concurrent with those of Reimer et al who included 53 patients with ASA > 1 undergoing elective surgery.…”
Section: Plos Onecontrasting
confidence: 73%
“…In patients undergoing curative treatment for colorectal cancer, HRV does not only seem to influence cancer prognosis. A recent study showed that patients with lower HRV have more intraoperative blood loss and more, and more severe, postoperative complications [15].…”
Section: Introductionmentioning
confidence: 99%
“…Patients who have diminished physiologic reserve are less able to respond to stressors, which translates to less variability in parameters such as blood pressure and heart rate. 29 For example, lower preoperative heart rate variability has been associated with greater risk of hypotension following anesthesia induction, as well as postoperative cardiac events. 30,31 While patients who underwent prehabilitation did have non-significantly increased heart rate variability, they demonstrated significantly increased variability in blood pressure, with an overall increase in systolic and diastolic blood pressure an hour into surgery compared to both other groups.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that in order to reduce the chances of inflammatory conditions in the wake of surgery, it might be worthwhile to provide some activities that increase the vagal activity prior to the surgery (“pre-habilitation”). This would increase the patient’s vagal inflammatory resistance allowing him/her to cope with the event of surgery and the associated stress more effectively (Geiss et al, 2005; Laitio et al, 2007; Mazzeo et al, 2011; Bravi et al, 2012; Bohanon et al, 2015; Ernst et al, 2017; Reimer et al, 2017; Yang et al, 2018). An additional argument in favor of this conclusion comes from our observation that patients with strong pre-surgery values make the best use of the rehabilitation in improving their vagal activity.…”
Section: Discussionmentioning
confidence: 99%